McKenna, ready to fly! - Casanova, Mary (American Girl Pub., 2012)
When Seattle fourth-grader McKenna Brooks' cast comes off she dives back into gymnastics training in hopes of making the competitive team, but after volunteering at a therapeutic horseback riding center, she considers broadening her interests.